Racial Differences in the Association Between Apolipoprotein E Risk Alleles and Overall and Total Cardiovascular Mortality Over 18 Years - Rajan, Kumar B. (J Am Geriatr Soc, 2017)
OBJECTIVES: To examine the difference in the association between apolipoprotein (APO)E allele and overall and cardiovascular mortality between African Americans (AAs) and European Americans (EAs). DESIGN: Longitudinal, cohort study of 18 years. SETTING: Biracial urban US population sample. PARTICIPANTS: 4,917, 68% AA and 32% EA. MEASUREMENTS: APOE genotype and mortality based on National Death Index. RESULTS: A higher proportion of AAs than of EAs had an APOE ε2 allele (ε2ε2/ε2ε3/ε2ε4; 22% vs 13%) and an APOE ε4 allele (ε3ε4/ε4ε4; 33% vs 24%). After adjusting for known risk factors, the risk of mortality was 19% less with the APOE ε2 allele (hazard ratio (HR) = 0.81, 95% confidence interval (CI) = 0.76–0.87), and the risk of cardiovascular mortality was 35% less (HR = 0.65, 95% CI = 0.58–0.76) than with the ε3ε3 allele. The risk of mortality was 10% greater with the APOE ε4 allele (HR = 1.10, 95% CI = 1.04–1.16), and the risk of cardiovascular mortality was 20% greater (HR = 1.20, 95% CI = 1.07–1.29) than with the ε3ε3 allele. No difference in the association between APOE allele and mortality was observed between AAs and EAs. CONCLUSION: The APOE ε4 allele increased the risk of overall and cardiovascular mortality, whereas the APOE ε2 allele decreased the risk of overall and cardiovascular mortality. There was no racial difference in the association between these alleles and mortality. J Am Geriatr Soc 65:2425–2430, 2017.